The Role of Customer Service in Increasing Customer Satisfaction of Islamic Banking in the Digitalization Era at BSI Sepanjang Wonocolo - Halim, Dinna Ahsanti; Latifah, Fitri Nur (Jurnal Iqtisaduna, 2025)
This study aims to examine the role of customer service in enhancing customer satisfaction within Sharia banking in the digital era, using Bank Syariah Indonesia (BSI) Sepanjang Wonocolo Branch as a case study. Amid rapid technological advancements and the digitalization of banking services, the function of customer service has become increasingly vital in maintaining service quality and fostering strong customer relationships. A qualitative approach was employed, utilizing observations, in-depth interviews, and document analysis to collect data. The findings reveal that customer service personnel at BSI Sepanjang Wonocolo not only provide transactional assistance and information but also actively educate customers on digital banking tools, respond promptly to complaints, and maintain effective and personalized communication. These efforts have been shown to contribute significantly to improvements in customer satisfaction and loyalty. Therefore, optimizing an adaptive customer service role in line with digital developments is essential for sustaining customer trust in the transformational landscape of Sharia banking.